Orthosis Treatment for Patients with Congenital Hip Dislocation - Rakotonandrianina, Manohisoa Nomena Harisambatra; MG., Ando Tatiana Ranaivondrambola; Tata, Tsiahoana Jean Floris; Solofomalala, Gaítan Duval (Faculty of Medicine, Universitas Airlangga, 2023)
Background: Congenital dislocation of the hip is currently a public health and socioeconomic problem. Delayed treatment impairs the functional prognosis of the affected hip and increases the need for surgical treatment. Aim: To evaluate the therapeutic results of the treatment by orthosis and the cost of the treatment. Material and Methods: This retroprospective descriptive study was carried out at the CHUAM of Antananarivo and the CRMM of Antsirabe on patients with congenital hip dislocation treated with braces; from January 2017 to August 2021. Results: Forty-eight cases were retained during this study. A female predominance was mentioned with a sex ratio of 0.45 and an average age of 7.8 ± 5.5 months at the beginning of the treatment. A left dislocation was observed in 27.1% of cases. Twenty-nine patients were treated with abduction pants. A recentered femoral head showing a good result was present in 37 patients. Five dislocations were observed at follow-up, and 5 residual subluxations. No cases of avascular necrosis of the femoral head have been reported. The total cost of orthosis treatment was on the average of 138.554,5 ± 51.678,8 Ariary. Conclusion: The age at the start of treatment and the duration of treatment influence the therapeutic outcome. The cost of orthosis treatment was affordable. If the treatment started earlier, the functional prognosis would be better.